The Pathogenic Body in Colonial Science, 1901-1913 - Garcia Jr., Felino S. (Philippine Social Sciences Review; Vol 65, No. 1, Jan-June 2013, Ed. Rolando Esteban, 2014)
This paper is a postmodernist reading of how laboratory science and its textual, discursive form, the scientific paper, connived in the construction of the Filipino body. It aimed to show how the knowledge-power relations played out toward the pathologization of the body, how forms of power were lodged in such institutions as the laboratories of the Bureau of Science, and how disciplinary procedures and technics reflected cultural and racial distinctions. It drew largely its primary sources from the scientific papers published in the Philippine Journal of Science and examined these sources through a Foucauldian lens. The scientific paper textualized laboratory work that projected a diseased, unhygienic Filipino body that needed to be controlled and reformed vis-à-vis American corporeality that was disciplined, ennobling, and a product of evolutionary growth. Its claims for truth, accuracy, and authority on the one hand, and the role that it played in Benevolent Assimilation on the one hand, justified intrusions into everyday life and the body through medical surveys and laboratory examinations for pathogens. Colonial science turned the Philippines into a laboratory and the Filipinos as participants in experiments that had a bearing on racism, including the rationalizations on fitness for self-government that was at once political, cultural, racial, and bodily.
Keywords: Colonial Science